The Role of Bursa Kerja Khusus (BKK) in Assisting The Absorption of Graduates Employment - Ain, Latifah; Ismiyati, Ismiyati (Economic Education Analysis Journal, 2021)
The purpose of this study was to determine the role of the BKK in assisting the absorption of graduate’s employment at SMK Negeri 1 Purwodadi. The research method used is descriptive with a qualitative approach. Sources of research data were obtained from 19 informants consisting of the Principal, Deputy Head of Public Relations, Chairman of BKK, Secretary of BKK, Treasurer of BKK, 14 graduates of SMK Negeri 1 Purwodadi. The technique of determining the informants used purposive sampling and snowball sampling. Data collection techniques using the librarian method and field study methods consisting of observation, interviews, a`nd documentation. The results revealed that the role of BKK in SMK Negeri 1 Purwodadi includes registration and data collection of job seekers who have completed their education or training; data collection of``to the needs of labor users or to be independent; offers to users of labor regarding the supply of labor; implementation of verification as a follow-up to the deliveries and placements that have been made; implementation of job fair activities and similar activities. From the BKK’s role, it was found that there were still graduates who had not been absorbed in the world of work. The conclusion of this study, the role of the BKK in assisting the absorption of graduate work at SMK Negeri 1 Purwodadi is in accordance with Binapenta Regulation No. Kep-1907 / PPTK-PKK / X / 2018.